Spinal and limb abnormalities in adolescents with intellectual disabilities - Lin, Jin-Ding; Lin, Pei-Ying; Lin, Lan-Ping; Lai, Chia-Im; Leu, Yii-Rong; Yen, Chia-Feng; Hsu, Shang-Wei; Chu, Chi-Ming; Wu, Chia-Ling; Chu, Cordia M. (Research in developmental disabilities, 2010)
There are not many studies pertaining to the spinal or limb abnormalities in people with intellectual disabilities, without a clear profile of these deformities of them, efforts to understand its characters and improve their quality of life will be impossible. Therefore, this paper aims to describe the prevalence and related factors of spinal and limb abnormalities in adolescents with intellectual disabilities.
Gesehen am 28.03.2023